Achieving the Bank of Japan's Inflation Target - Hong, Gee Hee.; Anand, Rahul; Hul, Yaroslav (Washington, D.C. : International Monetary Fund, 2019)
The Bank of Japan has introduced various unconventional monetary policy tools since the launch of Abenomics in 2013, to achieve the price stability target of 2 percent inflation. In this paper, a forward-looking open-economy general equilibrium model with endogenously determined policy credibility and an effective lower bound is developed for forecasting and policy analysis (FPAS) for Japan. In the model's baseline scenario, the likelihood of the Bank of Japan reaching its 2 percent inflation target over the medium term is below 40 percent, assuming the absence of other policy reactions aside from monetary policy. The likelihood of achieving the inflation target is even lower under alternative risk scenarios. A positive shock to central bank credibility increases this likelihood, and would require less accommodative macroeconomic policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet